Characterization of Crude and Partially Purified Lipase from Geotrichum candidum Obtained with Different Nitrogen Sources. (5th August 2016) - Maldonado, Rafael Resende; Pozza, Eduardo Luiz; Aguiar‐Oliveira, Elizama; Costa, Fátima Aparecida Almeida; Maugeri Filho, Francisco; Rodrigues, Maria Isabel
Abstract: Lipases from Geotrichum candidum were produced in two different medium: A = 12 % (w/v) clarified corn steep liquor (CCSL) + 0.6 % (w/v) soybean oil (SO) and B = 3.5 % (w/v) yeast hydrolysate (YH) + 0.7 % (w/v) SO. Lipases were partially purified from both media by hydrophobic interaction chromatography using 3.0 mol L −1 of NaCl as mobile phase, and they were characterized in the crude and partially purified forms. The recovery of lipase activity from CCSL and YH via HIC were 96 and 94.3 %, and the purification factors were 44.3 and 86.7‐fold, respectively. All evaluated lipases had similar optimum pH (7.0–7.7), but, for the CCSL crude lipase, optimum temperature (47 °C) was 10 °C higher than others lipases evaluated. CCSL crude lipase possessed a higher thermo stability than YH crude lipase, e.g., at 37 °C (pH 7.0) the half‐life of CCSL crude lipase was 19.25 h and at pH 8.0 (30 °C) the half‐life was 48 h, which are five and ten times higher than with YH crude lipase, respectively. On the other hand, the YH crude lipase possessed a higher catalytic constant ( k cat = 2.3 min −1 ) but with almost the same catalytic efficiency ( K m / k cat = 32.12 mg mL min −1 ) in relation to CCSL crude lipase. The lipases differ in biocatalytic properties between substrates, suggesting that the two lipases can be employed for different applications.